SOME PROBLEMS OF THE GRAVITY TRANSFORMATIONS CALCULATION - DUBOVENKO, Yu. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
An exact gravity transforms in regional studies is provided by the solution of nonlinear boundary Alexidze problem for the gravity potential. Its substitution by the appropriate problem for Laplace’s equation generates an errors, estimated in the paper. The numerical modeling of the last problem has shown, that accuracy of its solution extremely depends on the problem’s conditioning, approximations of required gradient direction, parameters of numerical calculus and direction of external normal, along which the proper derivatives are calculated.